(untitled) (KYAMC Journal, 2019)
Background: Urinary Tract Infection (UTI) is the second leading cause of bacterial infection worldwide. More female are affected compared to male, particularly in their reproductive age group. Untreated and repeated UTI cases lead to health complication and antimicrobial resistance. Objective: To know the proportion of UTI among women in child bearing age group in Rajshahi and also to know the influence of socio-demographic parameters on UTI incidence in this region. Methodology: A cross sectional descriptive study was conducted on women in their reproductive age group (15-45 years) in Institute of Biological Sciences (IBSc), Rajshahi University and Rajshahi Medical College (RMC) from July 2014 to June 2017 where mid-stream urine samples were collected and cultured following all standard procedure. Positive cultures were compared with sociodemographic parameters to know their association with UTI cases. Result: Out of Total 450 patients screened for UTI, 151 (33.55%) were culture positive. Married women showed the highest rate of UTI 95 (62.91%) compared to single and widowed/divorced women which was 49 (32.4%) and 7(4.6%) respectively. Pregnancy and diabetes showed greater incidence or association with UTI which was 116 (76.8%) and 93 (61.59%) respectively. In all cases combined, symptomatic UTI was much higher than asymptomatic bacteriuria 54 (35.7%). Good hygiene and cleanliness associated with use of sanitary napkins and latrines have greatly reduced UTI rates among women which were 31 (20.5%) and 27 (17.8%) respectively. Conclusion: UTI has a high rate among women in their childbearing age, particularly when associated with pregnancy and diabetes. Good personal hygiene and awareness can greatly reduce its incidence and prevent further complications and most importantly antimicrobial resistance. KYAMC Journal Vol. 10, No.-3, October 2019, Page 156-159